(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Fifteen vertical electrical soundings using the Schlumberger configuration with a current electrode spacing of AB/2 = 100m were conducted in Biu town, northeastern Nigeria. The field data were analyzed with IX1D inversion software to estimate porosity and identify porous zones. Results indicated four distinct layers with different thicknesses, resistivities, and weathering levels. The first layer is identified as alluvial topsoil, the second as weathered basalt, the third as fractured basalt, and the fourth as fresh basement. Resistivity values for the layers are: 2.16 to 149.00 Ωm for the topsoil, indicating porosity from secondary porosity or water content; 3.60 to 244.00 Ωm for weathered basalt; 16.50 to 372.20 Ωm for fractured basalt; and 55.04 to 449.75 Ωm for the fresh basement, reflecting high resistivity consistent with unaltered rock.